2023
DOI: 10.1097/hc9.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue insulin resistance exacerbates liver inflammation and fibrosis in a diet-induced NASH model

Abstract: Background: Insulin regulates various biological processes in adipocytes, and adipose tissue dysfunction due to insulin resistance in this tissue plays a central role in the development of metabolic diseases, including NAFLD and NASH. However, the combined impact of adipose tissue insulin resistance and dietary factors on the pathogenesis of NAFLD-NASH has remained unknown. Methods and Results: 3′-phosphoinositide–dependent kinase 1 (PDK1) is a serine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Whereas we focused on TSP-1 as a secreted protein whose expression is altered in adipose tissue of our MASH model (A-PDK1KO mice) and we showed that systemic TSP-1 de ciency ameliorates liver brosis in this model, we did not de nitively determine the cell source of the TSP-1 responsible for the promotion of liver brosis. Although TSP-1 is expressed at a higher level in adipose tissue than in the liver 24 , TSP-1 expression is also upregulated in the liver of A-PDK1KO mice 14 as well as in that of patients with chronic liver disease accompanied by brosis 35 . These ndings suggest that TSP-1 derived from certain cell types in the liver as well as that produced by adipocytes may contribute to the pathogenesis of MASH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas we focused on TSP-1 as a secreted protein whose expression is altered in adipose tissue of our MASH model (A-PDK1KO mice) and we showed that systemic TSP-1 de ciency ameliorates liver brosis in this model, we did not de nitively determine the cell source of the TSP-1 responsible for the promotion of liver brosis. Although TSP-1 is expressed at a higher level in adipose tissue than in the liver 24 , TSP-1 expression is also upregulated in the liver of A-PDK1KO mice 14 as well as in that of patients with chronic liver disease accompanied by brosis 35 . These ndings suggest that TSP-1 derived from certain cell types in the liver as well as that produced by adipocytes may contribute to the pathogenesis of MASH.…”
Section: Discussionmentioning
confidence: 97%
“…3′-Phosphoinositide-dependent kinase 1 (PDK1) is a serine-threonine kinase that plays a central role in insulin signal transduction by phosphorylating and activating the downstream kinase Akt. We have previously shown that adipocyte-speci c PDK1 knockout (A-PDK1KO) mice manifest a hepatic histology reminiscent of MASH in addition to systemic insulin resistance and related metabolic disorders 6,13,14 .…”
Section: Introductionmentioning
confidence: 99%